Oral consumption of cinnamon enhances the expression of immunity and lipid absorption genes in the small intestinal epithelium and alters the gut microbiota in normal mice. (October 2018) - Kim, Jong-In; Lee, Ju-Hoon; Song, Youngju; Kim, You-Tae; Lee, Youn-Hyung; Kang, Hee
Graphical abstract: Highlights: Cinnamon increases the expression of immunity and metabolism genes in the small intestinal epithelium. Cinnamon increases luminal IgA levels in the small intestine. Cinnamon decreases the presence of the phylum Proteobacteria in the large intestine. Abstract: Because cinnamon is orally ingested, its biological activity is likely to influence the small intestinal epithelium and the microbiota along the intestinal tract. We investigated small intestinal epithelial gene expression associated with immunity and lipid metabolism and measured IgA level in the small intestines and sera of mice fed cinnamon. We also analyzed microbial changes in the small and large intestines and feces using pyrosequencing of the 16 s rRNA gene. Cinnamon increased the gene expression of Muc2, RegIIIγ, and Pigr, which are necessary for defense against gut bacteria. It also increased the gene expression of GATA4 and Slc27a2, which are implicated in lipid absorption. Cinnamon increased luminal IgA level but not serum IgA and decreased the class Gammaproteobacteria (classified within the phylum Proteobacteria ), particularly the genus Pseudomonas, in the large intestine. Cinnamon thus affected immunity and lipid absorption in the small intestinal epithelium and microbial composition in the intestines.